Química y Farmacología del Piper aduncum L. ("Matico") - Lock, Olga (2004)
This review article covers the present knowledge on the chemistry and biological activities of Piper aduncurn and its synonyms P. angustifoliurn and P. elongaturn. More than 50 compounds have been isolated from these species, which can be grouped as chromenes, phenylpropanoids, benzoic acid derivatives and flavonoids. The biological activities of the crude extracts, and the compounds isolated from them, are discussed.